The effectiveness of media-based family education on healthy lifestyle behaviors among adolescents in Gunungkidul as a Strategy for preventing stunting - Baiquni, Fahmi; Hersipa, Lulung Lanova; Karuniawati, Benny (Jurnal Cakrawala Promkes, 2025)
Stunting remains a major public health issue in Indonesia, particularly in regions such as Gunungkidul, where prevalence exceeds the national average. Most interventions focus on the first 1,000 days of life, with limited involvement of adolescents, despite their potential role as future parents and family health advocates. This study aimed to evaluate the effectiveness of media-based family education in improving adolescents’ healthy lifestyle behaviors as part of a strategy to prevent stunting. A quasi-experimental design with a one-group pretest–posttest approach was conducted involving 35 adolescents aged 12–15 years and their parents in Gunungkidul. The intervention consisted of adolescent training, parental education, and family habit monitoring over four weeks, utilizing educational videos, posters, and interactive sessions. Data were collected through observations and structured family diaries, then analyzed with the Mann–Whitney test and effect size calculation. Results showed a significant increase in adolescents’ healthy lifestyle behaviors, including balanced nutrition (13.2 ± 2.5 vs. 17.1 ± 1.8, p < 0.001; d = 1.79) and handwashing with soap (12.5 ± 2.2 vs. 16.3 ± 1.7, p = 0.001; d = 1.93). Family diaries also indicated improvements in parents’ meal planning and adolescents’ consistent implementation of clean and healthy living practices. These findings suggest that media-based family education effectively strengthens adolescent–parent collaboration, improves health communication, and fosters sustainable household behaviors relevant to stunting prevention. The integration of adolescent-focused modules into school and community health programs is recommended to support national efforts aimed at reducing stunting.